GENERAL ASPECTS OF THE PROOF PROCESS IN CRIMINAL PROCEEDINGS (Eureka Journal of Humanities and Social Research, 2026)
Evidence plays a very important role in criminal proceedings. If the evidence gathering process proves fruitless and it cannot be established who committed the crime and under what circumstances, then the objectives of the criminal proceedings can be considered unfulfilled. This article analyzes issues related to procedural activities for proving evidence in criminal proceedings, which consist of collecting, verifying, and evaluating evidence in order to establish the circumstances relevant to the lawful, reasonable, and fair resolution of the case.
Keywords: Evidence in criminal proceedings, subject matter of evidence, limits of evidence, circumstances to be established in a criminal case, system of general conditions for evidence, subjects of evidence.